Surface arrays on the cell wall of Spirillum metamorphum. - Beveridge, T J (1975)
A complex and easily disrupted arrangement of macromolecules was present on the outer (lipopolysaccharide) membrane of the cell wall of Spirillum metamorphum. Separation of the arrays from the cell and spontaneous reassembly into regularly structured complexes usually occurred during preparation for electron microscopy. Freeze etchings, thin sections, and optical diffraction analysis of negatively stained fragments indicated that they consisted of two sets of a thin layer which was studied with 3-nm particles arranged in a loose (OL). The OSL consisted of a hexagonal arrangement of 8-nm disks and the OL of a thin layer which was studied with 3-nm particles arranged in a loose rectangular manner. The OSL of reassembled fragments displayed numerous broken delta-linkers between units and a center-to-center spacing of half the expected distance, which suggests that an interdigitation of two OSL arrays had occurred. The observations combined with freeze etchings and thin sections of whole cells suggested a possible reassembly mechanism. The normal surface arrangement of these layers on cells was thought to consist of the OL overlying one set of OSL which was loosely adherent to a thin amorphous backing layer.